Time deterministic routing algorithm and protocol based on time-varying graph over the space-ground integrated network - Hongyan LI; Tao ZHANG; Jingqian ZHANG; Keyi SHI; Pengcheng ZENG (Tongxin xuebao)
In terms of the difficulties to construct the end-to-end path and improve the utilization of network resources,caused by the time-varying multi-dimensional resources and diverse services over the space-ground integrated networks,the time-varying graph-based time deterministic routing algorithm and protocol for the space-ground integrated network was proposed.Firstly,a time-varying continuous graph model was constructed to describe the spatial and temporal attributes of multi-dimensional resources,such as the topology,link connectivity opportunities,node caching and so on.Then,a service-oriented time deterministic routing algorithm was proposed.According to the calculation rules of link cumulative traffic,and the constraints of node flow conservation and cache,the time-varying path with the shortest transmission delay was constructed.After that,a delay-guaranteed time deterministic routing protocol was designed by combining the proposed routing algorithm with both the segment routing technology and the time sensitive network technology,which supported the dynamic topology discovery,the efficient calculation of deterministic routing and the timing forwarding of data packets on the time-varying network.The simulation results show that,compared with the routing algorithm based on snapshot graph and contact graph,the proposed routing algorithm has higher link resource utilization rate and the packet successful delivery rate by jointly using link and node storage resources by association,and ensures the end-to-end transmission delay of services.